“You’ll suffer a lot, but you will survive”: Maryse Condé’s i, tituba, black witch of Salem as a Bildungsroman - Nunes, Ruan (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2016)
While Spivak’s question regarding the voice of the subaltern is still the topic of several academic debates, the presence of the subaltern in postcolonial studies cannot be neglected or overlooked. Maryse Condé’s rewriting of Tituba gives voice to a woman whose history has been erased and forgotten. Taking into consideration that Condé’s I, Tituba, Black Witch of Salem foregrounds issues of identity, sexuality and gender, this paper analyses the novel as a Bildungsroman in which Tituba is finally able to describe her coming of age and her experiences.